Two‐Dimensional MXene as a Nanofluidic Anolyte Additive for Enhancing Performance of Vanadium Redox Flow Batteries. Issue 12 (27th October 2022) - Vala Mizrak, Ali; Ehring, Jonathan C.; Shekhirev, Mikhail; Lord, Robert W.; Aküzüm, Bilen; Singh, Pushpendra; Gogotsi, Yury; Kumbur, E. Caglan
Abstract: In this work, Ti3 C2 T x MXene was investigated as a nanofluidic anolyte additive in vanadium redox flow batteries to improve the sluggish kinetics of V 2+ /V 3+ redox reaction. Numerous electrochemical tests under flow and static conditions were performed to demonstrate the effectiveness of MXenes for VRFB applications. Pressure drop tests and morphology analysis were also conducted to better understand the hydraulic effects of MXene addition into the anolyte. The nanofluidic anolytes with the concentration of 0.10 and 0.15 wt% showed the best electrochemical performance, although the former induced less aggravated hydraulic effects within a reasonable pressure drop range. At a current density of 200 mA cm −2, the nanofluidic analyte containing 0.10 wt% MXene was able to utilize 67 % of the theoretical capacity. Contrarily, with the pristine anolyte, only 10 % of the theoretical capacity could be utilized due to excessive losses. Moreover, the energy efficiency up to 74 % is observed for the nanofluidic electrolyte, which is an increase of 25 % compared to the pristine anolyte. Primarily, the enhanced battery performance was attributed to the improved electrocatalytic activity towards the anodic V 2+ /V 3+ redox reaction. Furthermore, a dynamic, web‐like, flowing electrode network is shown to increase the mass transport capacity of porous carbon felt electrodes by creating additional, abundant, and electrochemically active surfaces within the pores. Abstract : Filling the gaps : MXene particles were utilized as a nanofluidic anolyte additive in vanadium redox flow batteries. Ti3 C2 T x provided the formation of a continuous and dynamic web‐like structure flowing through highly porous carbon felt electrode, which significantly facilitated the anodic V 2+ /V 3+ redox reactions by increasing electrochemically active surface area and improving mass transport capacity.